Olexiy Petrov and the «conspirators of Kyiv» - Борзенко, Олександр Іванович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article explores the memories of О. Petrov about his part in a covert organization. Memoirist arguing with another member of this organization – M. Kostomarov. Petrov offers an alternative version of the ancient event in which he appears hostage to circumstances, victim of misunderstanding and indifference. In the interpretation of his life О. Petrov used the inherent romanticism practice of rethinking and clarifying biographical material.